Diagnosing the Linear Periodicity Dynamics of ENSO for Its Two Spatiotemporal Modes - Ren, Hong‐Li; Wang, Run (Geophysical research letters, 2023)
The El Niño–Southern Oscillation (ENSO) is mainly manifested as the quasi‐biennial (QB) and low‐frequency (LF) coupled modes centered at different longitudes. Based on the recharge oscillator framework, we propose a new method to diagnose the linear periodicity dynamics of spatiotemporally diverse ENSOs, for example, the two coupled modes, to which the traditional Wyrtki index method is ineligible. This method is applied to reanalysis data sets and models and validated by comparisons with the Wyrtki index, which shows that the periodicity of the LF mode is dominated by the thermocline feedback (TH) and effectively reproduced by models, whereas the periodicity of the QB mode is equally driven by the TH and zonal advective feedback (ZA) and poorly simulated in most models due to the insufficient ZA simulations. The new method provides an effective tool for a deeper understanding of the multi‐timescale nature of diverse ENSOs and improving their representations in future models. Plain Language Summary The El Niño–Southern Oscillation (ENSO) has two relatively separated main period bands, viz., the 3–7‐year low‐frequency (LF) and 2–3‐year quasi‐biennial (QB), which have been found to be accompanied by the eastern‐Pacific and central‐Pacific spatial types of ENSO sea surface temperature anomalies. What controls such periodicity is a fundamental question in ENSO dynamics. In this study, we propose a new method to diagnose the ENSO linear periodicity dynamics and the role of key feedbacks in determining ENSO periods due to the limitation of the traditional volume‐averaged scheme concerning ENSO pattern diversity. Our method, validated by comparison with the Wyrtki period index originating from the ENSO recharge oscillator framework, clearly shows that the thermocline feedback dominates in shaping the periodicity of the LF mode, whereas its role is equal to the zonal advective feedback in the QB mode. Most of the Coupled Model Intercomparison Project 6 models can effectively reproduce the linear periodicity of the LF mode following the canonical ENSO dynamics but struggle with capturing that of the QB mode. This new method and its related results could increase our understanding of the dynamics of the spatiotemporal diversity of ENSO. Key Points A new method is proposed and validated to diagnose the linear periodicity dynamics of The El Niño–Southern Oscillation (ENSO) for its both quasi‐biennial (QB) and low‐frequency (LF) spatiotemporal modes The thermocline feedback dominates periodicity of the LF mode, but its role is equal to the zonal advective feedback in the QB mode Most Coupled Model Intercomparison Project 6 models can effectively reproduce linear periodicity of the LF mode like canonical ENSO dynamics, but struggle with the QB mode